2010
DOI: 10.2147/ndt.s7637
|View full text |Cite
|
Sign up to set email alerts
|

Management of depression in elderly stroke patients

Abstract: Poststroke depression (PSD) in elderly patients has been considered the most common neuropsychiatric consequence of stroke up to 6–24 months after stroke onset. When depression appears within days after stroke onset, it is likely to remit, whereas depression at 3 months is likely to be sustained for 1 year. One of the major problems posed by elderly stroke patients is how to identify and optimally manage PSD. This review provides insight to identification and management of depression in elderly stroke patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 110 publications
(139 reference statements)
3
48
0
5
Order By: Relevance
“…Наиболее патогенетически оправданным является назначение антидепрессантов, что доказано во многих плацебо-контролируемых исследованиях [6,7]. Исполь-зование антидепрессантов может улучшить не только эмоциональное состояние, но и когнитивные функции, привести к более быстрому и существенному восстанов-лению утраченных неврологических функций, улучить качество жизни [7,8].…”
Section: лечение пдunclassified
See 1 more Smart Citation
“…Наиболее патогенетически оправданным является назначение антидепрессантов, что доказано во многих плацебо-контролируемых исследованиях [6,7]. Исполь-зование антидепрессантов может улучшить не только эмоциональное состояние, но и когнитивные функции, привести к более быстрому и существенному восстанов-лению утраченных неврологических функций, улучить качество жизни [7,8].…”
Section: лечение пдunclassified
“…Исполь-зование антидепрессантов может улучшить не только эмоциональное состояние, но и когнитивные функции, привести к более быстрому и существенному восстанов-лению утраченных неврологических функций, улучить качество жизни [7,8].…”
Section: лечение пдunclassified
“…Antidepressants are most studied strategies and the best studied agents are citalopram, nortriptyline, fluoxetine, and sertraline. [12] Major goals of PSD treatments include reducing depressive symptoms and getting complete remission (no longer meeting baseline criteria for depression). [13] Meta-analysis found antidepressants to be significantly effective in reducing depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] However, there is no clear evidence to recommend antidepressants in terms of getting complete remission of depression when assessed by Diagnostic and Statistical Manual of Mental Disorders (DSM) or Hamilton Depression Rating Scale (HAMD). [13,15] Although selective serotonin reuptake inhibitors (SSRIs) are gaining popular as 1st-line treatment for PSD and late-life depression, [12] but no study provides conclusive evidence on the superiority of SSRIs over any other treatments, nor strong data recommending 1 particular SSRI over another for PSD management.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Hackett et al found no superiority over control intervention for psychotherapy alone 13 . Although selective serotonin reuptake inhibitors (SSRIs) are gaining popularity as first-line treatment for PSD and late-life depression 12,16 , neither studies provide conclusive evidence with respect to the superiority of SSRIs over any other treatments nor strong data recommend one particular SSRI over another for PSD management.…”
mentioning
confidence: 99%